1977
DOI: 10.1159/000162869
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Steroid Structure in Relation to Liver Metabolism during Endotoxin Lethality in Mice

Abstract: The influence of a number of steroid molecules on hepatic metabolism was determined in relationship to their ability to alter endotoxin lethality in intact mice. Progesterone, testosterone, estradiol, pregnenolone-16-α-carbonitrile and spironolactone did not alter endotoxin lethality, liver glycogen or tryptophan pyr-rolase (TP) levels; all these materials increased liver tyrosine transaminase (TT) levels most probably due to mediation by endogeneously liberated glucocorticoid hormones. Aldosterone and deoxyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…While mifepristone inhibits both glucocorticoid and progesterone receptors, its protection against lethality is likely due to its ability to inhibit glucocorticoid receptors as endotoxin lethality in mice was diminished by dexamethasone but not progesterone (Lazar et al, 1977). Using this approach, which spares the adrenal but targets the action of hormones derived from the adrenal cortex, we found that mifepristone failed to influence movement-evoked hyperalgesia at a dose that enhanced the lethal effects of LPS.…”
Section: Discussionmentioning
confidence: 87%
“…While mifepristone inhibits both glucocorticoid and progesterone receptors, its protection against lethality is likely due to its ability to inhibit glucocorticoid receptors as endotoxin lethality in mice was diminished by dexamethasone but not progesterone (Lazar et al, 1977). Using this approach, which spares the adrenal but targets the action of hormones derived from the adrenal cortex, we found that mifepristone failed to influence movement-evoked hyperalgesia at a dose that enhanced the lethal effects of LPS.…”
Section: Discussionmentioning
confidence: 87%